NLRP3 Inflammasome-Dependent Increases in High Mobility Group Box 1 Involved in the Cognitive Dysfunction Caused by Tau-Overexpression - Zhao, Yan; Tan, Si-Wei; Huang, Zhi-Zhong; Shan, Fa-Bo; Li, Ping; Ning, Ya-Lei; Ye, Shi-Yang; Zhao, Zi-Ai; Du, Hao; Xiong, Ren-Ping; Yang, Nan; Peng, Yan; et al. (Frontiers in Aging Neuroscience, 2021)
Tau hyperphosphorylation is a characteristic alteration in a range of neurological conditions including traumatic brain injury (TBI) and neurodegenerative diseases. The treatments targeting High mobility group box protein 1 (HMGB1) displayed neuroprotective effects in these neuropathologic conditions. However, little is known about interactions between hyperphosphorylated tau and HMGB1 in neuroinflammation. We established TBI model by controlled cortical impact and tau hyperphosphorylation model by injection of the virus encoding human P301S tau in mice and performed immunoflurescent and western boltting analysis and behavioral tests to clarify the interaction between phorsphorylated tau (p-tau) and HMGB1 levels. NLRP3-/- mice and HMGB1 inhibitor, glycyrrhizin, were used to explore the therapeutic strategy for diseases with p-tau overexpression. We demonstrated the elevations in p-tau and HMGB1 in spatial memory-related brain regions in mice with TBI or tau-overexpression and NOD-like receptor family, pyrin domain containing 3 (NLRP3) inflammasome activation by the increases in ASC specks, the activation of Caspase1, and IL-1β. Compared to wild-type mice with tau-overexpression, downregulation of p-tau and HMGB1 was observed in NLRP3-/- mice, indicating HMGB1 alterations were NLRP3-dependent. Moreover, the treatment with glycyrrhizin at a late stage markedly reduced p-tau levels, improved the performances in Y- and T-maze and the ability to build a nest in tau-overexpressed mice, which revealed improvements in spatial memory and advanced hippocampal function. Our findings identify a trigger role for p-tau in modulation of neuroinflammation and spatial memory via an NLRP3-dependent manner, and suggest that the treatment with HMGB1 inhibitor may be a better therapeutic strategy for tauopathies.